2023
DOI: 10.4103/ijo.ijo_2709_22
|View full text |Cite
|
Sign up to set email alerts
|

Lid wiper epitheliopathy in symptomatic and asymptomatic dry eye subjects

Abstract: Purpose: Lid wiper epithliopathy (LWE) was stuided in symptomatic and asymptomatic dry eye subjects. This is the first such study to be conducted in the Indian population. LWE is a clinical condition associated with vital staining in the lower and upper eyelids on increased friction of the lid margin over to the cornea. Our aim was to study LWE in symptomatic and asymptomatic (control) dry eye subjects. Methods: Out of 96 subjects screened, 60 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Kamath et al [11] reported that individuals with symptomatic dry eye disease had signi cantly more LWE (99.8%) than those without symptoms (73.3%), and symptomatic dry eye subjects had more severe LWE (56.6% of grade 3) than asymptomatic subjects (40% of grade 2) after grading the stained LWE, these percentages were greater than those of Korb's study, in which the prevalence of 76% of LWE among symptomatic dry eye subjects and the severity of Grade I and II were only 8% and 4%, respectively [26]. These results suggest that LWE may occur before the development of dry eye symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamath et al [11] reported that individuals with symptomatic dry eye disease had signi cantly more LWE (99.8%) than those without symptoms (73.3%), and symptomatic dry eye subjects had more severe LWE (56.6% of grade 3) than asymptomatic subjects (40% of grade 2) after grading the stained LWE, these percentages were greater than those of Korb's study, in which the prevalence of 76% of LWE among symptomatic dry eye subjects and the severity of Grade I and II were only 8% and 4%, respectively [26]. These results suggest that LWE may occur before the development of dry eye symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Each portion was evaluated separately from 0 to 3 points according to the following criteria: 0, entirely on the conjunctival side of the meibomian ori ces (MOs); 1, part of the ML touches the MOs; 2, the ML runs through all of the MOs; and 3, the ML runs on the eyelid margin side of the MOs [10]. Moreover, LWE was also evaluated by staining the lid wiper as previously described [11]. Staining as positive, and vice versa as negative.…”
Section: Evaluation Of the Lid Marginmentioning
confidence: 99%